2021
DOI: 10.1007/s00417-021-05442-3
|View full text |Cite
|
Sign up to set email alerts
|

Two-year results after combined phacoemulsification and iris-fixated phakic intraocular lens removal

Abstract: Purpose To describe and present results after a technique for cataract surgery combined with explantation of an iris-fixated phakic intraocular lens (IF-pIOL). Methods The medical records of all patients, who had undergone cataract surgery combined with IF-pIOL explantation and subsequent implantation of a posterior chamber IOL by the Single Incision Technique (SIT), were reviewed. Data collection included preoperative and postoperative corrected distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…However, the findings from published studies differ greatly. Both Gaurisankar et al and de Vries et al observed only a small rate of endothelial cell loss after the combined operation (mean cell loss of 3.5-9.4 %) [81,82]. In contrast, Vargas et al reported a considerably higher rate of endothelial cell loss (approx.…”
Section: Endothelial Cell Loss Due To Explantation Of Piols In Combin...mentioning
confidence: 93%
See 1 more Smart Citation
“…However, the findings from published studies differ greatly. Both Gaurisankar et al and de Vries et al observed only a small rate of endothelial cell loss after the combined operation (mean cell loss of 3.5-9.4 %) [81,82]. In contrast, Vargas et al reported a considerably higher rate of endothelial cell loss (approx.…”
Section: Endothelial Cell Loss Due To Explantation Of Piols In Combin...mentioning
confidence: 93%
“…Es bestehen jedoch große Unterschiede zwischen den veröffentlichten Studien. Gaurisankar et al sowie de Vries et al stellten nur einen geringen Endothelzellverlust nach der kombinierten Operation fest (mittlerer Verlust von 3,5 – 9,4%) 81 , 82 . Vargas et al berichteten hingegen über einen deutlich höheren Endothelzellverlust (ca.…”
Section: Endothelzellverlust Bei Explantation Phaker Intraokularlinse...unclassified
“…While the pIOL implantation itself can cause endothelial cell loss, it is usually limited to 4-8% [11,16,18,22,28,[58][59][60][61][62][63][64]. Larger losses can occur during pIOL explantation, alone or when combined with the cataract surgery [21,[65][66][67]. One study found a statistically significant endothelial cell loss (27% decrease in mean ECD) in patients with iris-fixated lenses when cataract was the indication for the combined surgery, but not in those who underwent the combined surgery because of endothelial cell loss, suggesting that endothelial damage due to phacoemulsification is the primary reason for the decreased ECD [10,67].…”
Section: Assessing Endothelial Cell Lossmentioning
confidence: 99%